2013
DOI: 10.1093/ckj/sft020
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access and infection prevention and control: a national survey of routine practices in Irish haemodialysis units

Abstract: BackgroundNational and international guidelines recommend the use of effective vascular access (VA) and infection prevention and control practices within the haemodialysis environment. Establishing an arterio-venous fistula (AVF) and preventing central venous catheter (CVC)-related infections are ongoing challenges for all dialysis settings. We surveyed VA and routine infection prevention and control practices in dialysis units, to provide national data on these practices in Ireland.MethodsA descriptive survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The fistula first initiative in the US is an excellent example where national policy underpinned by a strong regulatory framework has led a significant increase in AVF use and overall reduction in CVC [26][27][28]. In Ireland, McCann and colleagues reported a CVC prevalence of 52% in 2011 from results of a national survey of vascular access [20]. A direct comparison with our results 5 years later, highlight similar prevalence, suggesting that little has changed.…”
Section: Discussionsupporting
confidence: 64%
“…The fistula first initiative in the US is an excellent example where national policy underpinned by a strong regulatory framework has led a significant increase in AVF use and overall reduction in CVC [26][27][28]. In Ireland, McCann and colleagues reported a CVC prevalence of 52% in 2011 from results of a national survey of vascular access [20]. A direct comparison with our results 5 years later, highlight similar prevalence, suggesting that little has changed.…”
Section: Discussionsupporting
confidence: 64%
“…The fistula first initiative in the US is an excellent example where national policy underpinned by a strong regulatory framework has led a significant increase in AVF use and overall reduction in CVC [ 26 – 28 ]. In Ireland, McCann and colleagues reported a CVC prevalence of 52% in 2011 from results of a national survey of vascular access [ 20 ]. A direct comparison with our results 5 years later, highlight similar prevalence, suggesting that little has changed.…”
Section: Discussionmentioning
confidence: 99%
“…The structure, organisation, and delivery of HD vascular access care is a complex process and requires multidisciplinary team engagement with defined care pathways and embedded quality assurance. The survey by McCann et al identified a number of deficits in the health system including lack of availability of elective surgical beds and operating room slots, insufficient vascular access coordinators and access protocols which are likely to impact the timely and effective creation of AVFs [ 20 ]. Physician perspectives, as well as availability and experience of a vascular surgeon may also play a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…National and international guidelines along with national policy initiatives [6–9] recommend the use of arteriovenous fistula (AVF) whenever possible, as the risk of infections and other complications is highest among patients using central venous catheters (CVCs) [3, 10, 11]. Despite the dangers associated with CVC use, these devices remain the principal type of access in the majority of HD patients in Ireland [12, 13] and internationally [14].…”
Section: Introductionmentioning
confidence: 99%